Genetic predictors of poor prognosis in Portuguese patients with Juvenile Idiopathic Arthritis: data from Reuma.pt - Mourão, Ana (2015)
Copyright © 2015 Ana Filipa Mourão et al. This is an open access article distributed under the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.